Linking trap to G10 surface flashover in liquid nitrogen under DC voltage. (March 2022) - Zhang, Chuansheng; Ren, Chengyan; Zhou, Benzhe; Huang, Bangdou; Yang, Jinchuan; Li, Shuaikang; Man, Chenxi; He, Pengchen; Zhang, Cheng; Teng, Yuping; Shao, Tao
Highlights: The flashover voltage and current of G10 in LN2 are obtained through experiments and the flashover data is analyzed by Weibull model. The flashover process is observed by OES, and the surface evolution after G10 flashover is analyzed by optical microscope and FTIR. The relationship between polymer flashover and trap in LN2 is established through test of surface trap distribution and calculation of charge transport equation. Abstract: The insulation failure is a bottleneck to restrict the safe operation and development of direct current (DC) superconducting power devices. The solid–liquid flashover test is an important evaluation index, but the previous researches mostly focus on engineering application, and less involve in the mechanism analysis. As a characterization method for defects existing in the dielectric, the trap has been applied to the study of flashover to occur polymer surface in liquid nitrogen (LN2 ) in recent years. However, the mechanism of trap action in solid–liquid flashover is still confusing. Therefore, this paper carries out the following research. Firstly, the flashover voltage and current of glass epoxy laminate sheet (G10) in LN2 were obtained through experiments and analysis using the Weibull model in this paper. Secondly, the flashover process of G10 was monitored. The changes of G10 surface morphology and chemical bond before and after flashover were also observed. Finally, the relationship between polymer flashover and trap in LN2 was analyzed based on the surface trap distribution test and theoretical calculation of the charge transport equation. The results are beneficial to guide the selection and performance improvement of dielectric materials and the design of insulating structures in superconducting devices.